Winter Forage Legume Guide - Jose Dubeux; M. Wallau; Y.C. Newman; P. Munoz; K. Quesenberry (EDIS)
Winter legumes are important in forage production in Florida. They are frost tolerant and can supply highly nutritious feed during the winter and spring months. When properly inoculated, they supply nitrogen for their own growth and provide nitrogen for other plants growing with or following them. This document provides information on the different types of forage, its cultivation and maintenance. First published April, 1994.